Unlocking the 'Triple Dividend' of Resilience : Why Investing in Disaster Risk Management Pays Off - Overseas Development Institute; World Bank Group (Overseas Development Institute, London, and World Bank, Washington, DC, 2015)
The risk of a disaster can cause economic losses even before a disaster strikes. Investing in disaster resilience, therefore, can yield a ‘triple dividend’ by (1) avoiding losses when disasters strike; (2) unlocking development potential by stimulating innovation and bolstering economic activity in a context of reduced disaster-related background risk for investment; and (3) through the synergies of the social, environment and economic co-benefits of disaster risk management investments even if a disaster does not happen for many years.